A nucleus targetable fluorescent probe for ratiometric imaging of endogenous NO in living cells and zebrafishes. Issue 13 (10th June 2021) - Zhao, Liang; Huang, Zhenlong; Ma, Daqing; Yan, Yu; Zhang, Xinfu; Xiao, Yi
Abstract : A nucleus targetable fluorescent probe is developed based on a Hoechst and rhodamine dyad for ratiometric imaging of endogenous NO in living cells and zebrafishes. Abstract : Nitric oxide (NO) is an important cellular messenger molecule in the cardiovascular, nervous and immune systems. Real-time monitoring of NO activity in specific organelles of live cells is important to understand its biological function. In this work, a nucleus targetable ratiometric NO probe, Hoe–Rh-NO, is developed by linking Hoechst to rhodamine spirolactam. The Hoechst part conducts nucleus targeting and the rhodamine spirolactam senses NO. The two fluorophores constitute a NO switchable FRET system for ratiometric imaging. This newly developed probe Hoe–Rh-NO displays good nucleus targeting ability, high sensitivity and selectivity towards NO, low cytotoxicity and most importantly detects NO through ratiometric fluorescence imaging. By using Hoe–Rh-NO, we confirmed the presence of NO in the nucleus and detected endogenous NO during inflammation in cells and zebrafishes.